Efficacy of a standardized herbal formulation from Glycyrrhiza glabra L. as an adjuvant treatment in hospitalized patients with COVID-19: A Randomized Controlled trial - Saeed Soleiman-Meigooni; Nafiseh Hoseini Yekta; Hamid Reza Sheikhan; Mohammad Aminianfar; Ramin Hamidi-Farahani; Mousa Ahmadi; Ali Asgari; Mohammad Hasan Kazemi-Galougahi; Roja Rahimi (Journal of Ayurveda and Integrative Medicine, 2022)
Introduction: As no specific pharmacological intervention has been known for COVID-19, medicinal plants may be a suitable candidate for management of this disease. The aim of this study was to investigate the efficacy of a herbal syrup from licorice as an adjuvant treatment in hospitalized patients with COVID-19. Materials and methods: 213 hospitalized patients diagnosed with COVID-19 were assigned to receive either standardized licorice syrup as an adjuvant treatment plus standard care [Syrup Group (SYRUP), N = 91], or standard care alone [Standard Group (STANDARD), N = 104], for 7 days. The primary endpoint was duration of hospitalization in survivors. The secondary endpoints included 25% increase in oxygen saturation, C-reactive protein (CRP) difference and lymphocyte difference from baseline, number of death and number of patients transferred to ICU. Results: Mean duration of admission was 5.24 days in SYRUP and 7.14 days in STANDARD (p < 0.001). Oxygen saturation increased in 86 of 91 patients (94.5%) in the licorice group, compared to 83 of 104 patients (79.8%) in the control group (p = 0.002). There was no significant difference between the two groups in the number of patients died during hospitalization (p = 0.837). Five patients in SYRUP and 16 patients in STANDARD were transferred to ICU (p < 0.026). Mean reduction in CRP (p < 0.001) and mean increase in the number of lymphocytes (p = 0.008) in SYRUP were significantly higher than STANDARD. Discussion: Licorice syrup as an adjuvant treatment demonstrated promising results on duration of hospital admission, O2 saturation as well as inflammatory markers in COVID-19 patients; however, further clinical studies with larger sample size are suggested to achieve more conclusive results.